Urgensi Pendidikan Anak Usia Dini Dalam Al-Qur’an Dan Hadits Serta Relevansinya Dengan Kehidupan Di Masa Modern - Muhammad Saihu (Alif Lam: Journal of Islamic Studies and Humanities, 2022)
This study aims to understand the urgency of early childhood education in the Qur'an and hadith and their relevance to life in modern times. With library research, data is collected using the method of documenting the data found in various literature in accordance with the research theme that the author examines. The results of this study found that Islamic education aims to foster and shape the character, behavior, or morals of students by increasing students' faith, understanding, appreciation, and practice of Islamic teachings both in their circumstances and with many people. Al-Qur'an and hadith should be books that are guided by mankind in general without being limited by ethnicity and religion. Al-Qur'an is present as the key to success in both this world and the hereafter. Therefore, in the Qur'an, there are various solutions to every problem that humans face, including solutions in the teaching and learning process. In addition, there are also several methods offered by the Qur'an and hadith in fostering early childhood education. First, an educator must instruct his students on things that have positive values. Second, an educator in addition to being able to provide teaching must also be able to be a good role model. Because God is very angry with them (educators who can only theory without being able to apply it to everyday life. Third, the habituation method must be applied from an early age because the more accustomed to doing good things, the students will be more independent. Fourth, by telling the story students will easily remember the contents of the lesson, but what should be told is not fictitious things, because fictional stories do not contain historical value. Fifth, dialogue theory in addition to mental training also strengthens students in literacy